Pressure-assisted electrokinetic injection for the stacking of biogenic amines gives enhancement factor up to 1000 in CE with UV detection. Issue 18 (27th April 2022) - Yang, Xue; He, Lili; Xu, Zhongqi
Abstract : Pressure-assisted electrokinetic injection (PAEKI) was applied for stacking of positively charged biogenic amines (BAs) to improve the sensitivity of capillary electrophoresis (CE). Abstract : Pressure-assisted electrokinetic injection (PAEKI) was applied for stacking of positively charged biogenic amines (BAs) to improve the sensitivity of capillary electrophoresis (CE). It is well known that the essential step for PAEKI is finding a stationary state of the running buffer such that the movement of the running buffer due to electroosmotic flow (EOF) is counterbalanced by external pressure in the opposite direction of the EOF under a given electric field. In order to find the balance point systematically and integrally, we studied the velocity of the whole BGE in the capillary by the impetus of opposite direction pressure (−0.1 to −0.6 psi), and the velocity of EOF with different voltages. According to the two sets of linear data, the EOF of CE coupled with PAEKI could be counterbalanced at the opposite direction pressure (−0.1 psi) and voltage (7.8 kV). In this study, the injection time was extended up to 0.35 min for all BAs and 0.70 min for the direct ultraviolet (UV) detection of BAs. Compared with hydrodynamic injection (HDI), the enrichment factors for sample injection times of 0.35 min and 0.70 min were 480-fold and 970-fold, respectively. The limits of detection (LODs) (S/N = 3) of indirect and direct UV detection were respectively 8.7–24.3 nmol L −1 and 0.4–4.5 nmol L −1, which reaches the sensitivity of high-performance liquid chromatography-mass spectrophotometry (HPLC-MS). With appropriate sample dilution, PAEKI can be used in the analysis of BAs in chicken.